Low absolute bioavailability of oral naloxone in healthy subjects - Smith, Kevin; Hopp, Michael; Mundin, Gill; Bond, Simon; Bailey, Paul; Woodward, Jo; Bell, David (International journal of clinical pharmacology and therapeutics, 2012)
To determine the absolute bioavailability of naloxone from oral doses ranging from 5 mg to 120 mg. In this open-label study, 28 healthy subjects received naloxone 1 mg (0.4 mg/ml) as an intravenous infusion (reference treatment), and the following oral doses as prolonged release (PR) naloxone tablets: 5 mg, 20 mg, 40 mg, 80 mg and 120 mg. The pharmacokinetic characteristics of 40 mg administered per rectum were also investigated. Each subject received five of the seven treatments as single doses with a 7 day washout between doses. Pharmacokinetic blood sampling and safety monitoring were performed for 24 h after the intravenous dose, and 72 h after the oral and rectal doses. The mean absolute bioavailability of naloxone from the orally administered PR tablets was very low, ranging from 0.9% for the 5 mg dose to 2% for the 40, 80 and 120 mg doses, based on AUC(t) values. The pharmacokinetics of naloxone were linear across the range of oral doses. Where AUC(inf) values were calculated, these confirmed the results based on AUC(t) values (mean absolute bioavailability ranging from 1.9% to 2.2% for the 20 mg to 120 mg oral doses). The absolute bioavailability of naloxone was higher following rectal administration compared with oral administration, but was still low at 15%. The mean oral absolute bioavailability of naloxone in this study was ≤ 2% at doses ranging from 5 mg to 120 mg.